Unravelling galaxy components - Kennedy, Rebecca (2017)
This thesis aims to understand more about the developmental histories of galaxies and their internal components by studying the wavelength dependence of their spatial structure. I use a large sample of low-redshift galaxies with optical–near-IR imaging from the GAMA survey, which have been fitted with Sersic and Sersic + exponential functions in nine wavebands simultaneously, using software developed by the MegaMorph project. The first section of this thesis examines how the sizes and radial profiles of galaxies vary with wavelength. To quantify the wavelength dependence of effective radius I use the ratio, R, of measurements in two restframe bands. The dependence of Sersic index on wavelength, N, is computed correspondingly. I show that accounting for different redshift and luminosity selections partly reconciles variations between several recent studies. Dividing galaxies by visual morphology confirms the behaviour inferred using morphological proxies, although our quantitative measurements allow me to study larger and fainter samples. I then demonstrate that varying dust opacity and disc inclination can account for features of the joint distribution of R and N for late-type galaxies. However, dust does not appear to explain the highest values of R and N. The bulge-disc nature of galaxies must also contribute to the wavelength-dependence of their structure. The second section of this thesis studies radial colour gradients across the galaxy population. I use the multi-wavelength information provided by MegaMorph analysis of galaxy light profiles to calculate intrinsic colour gradients, and divide into six subsamples split by overall Sersic index (n) and galaxy colour.